Prevalence, serotypes and pathogenicity of Escherichia coli isolated from sheep meat - Yadav, Mahendra Mohan; Sharda, Rakesh; Sharma, Varsha (The Indian Journal of Animal Sciences, 2011)
Strains (49) of Escherichia coli were isolated from 100 samples ofmutton collected from dressed sheep carcasses by excision method. Biochemical characterization revealed minor variation from typical E.coli in fennentation of certain sugars. The isolates were typed into 12 different '0' serogroups. The most frequent serotype isolated was 0101, followed by 0152,076,023,0139,088,0110,0126,08,09,015 and 0133; 2 strains were untypable while 1 was rough. Whole bacterial cultures as well as cell free filtrate of randomly selected strains of 08, 088, 0101, 0133, 0139 and 0152 serogroup caused mortality in mice. Zoonotic significance of these strains is discussed.Â